HUBUNGAN ANTARA CITRA TUBUH DENGAN KEPERCAYAAN DIRI PADA REMAJA PELAJAR PUTERI DI KOTA DENPASAR - Wiranatha, Febian Dwiduonova; Supriyadi, Supriyadi (Jurnal Psikologi Udayana, 2015)
Adolescence is a transition  from childhood to adulthood. Physical, cognitive, social and emotional changes are happening in this stage. These changes make adolescents become aware about physical attractiveness on social interaction and develop some ideas about their body. Their body growth which not conform to their cultural standard and social reaction to a variety of body form, make girl adolecents become dissatisfied of their body and make a negative value about their body. A negative value about body also makes these girl adolescents become restless and have a low self-confidence. The aim of this study is to know relationship between body image and self confidence on girl adolescents. Cluster sampling is used in this study. Respondents are 492 students of some SMAN Denpasar, and it carried out in each selected SMAN Denpasar. This study use a body image scale by 38 items (reliability : 0,859) and a self confidence scale by 24 items (reliability : 0,881). Product moment is used to test hypothesis in this study and a simple regression is used to determine models of relationship and value of body image variable in explaining self-confidence variable. The results showed that there was a positive but relatively weak relationship between body image and self-confidence on girl adolescents students in Denpasar (r = 0,350; p < 0,05). The result is suitable with Centi’s idea (1997) that person who does not accept and does not satisfied to her body and appearance has low self confidence. The coefficient of determination (R2) obtained in the study was 0.122, which means the contribution of body image variable in explaining the self-confidence variable is 12.2 %, and it is a causal relationship.   Keywords: body image, self confidence, girl adolescents